2023
DOI: 10.1002/solr.202300754
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Friendly Perovskite‐Based Photovoltaics and Luminescence: Lead Less or Lead Free

Hong Zhu,
Gaoyu Liu,
Bihui Sun
et al.

Abstract: Lead‐based metal halide perovskite materials have been rapidly developed for light‐emitting diodes, solar cells and photodetectors owing to their excellent optoelectronic properties. Nevertheless, the presence of lead in these materials raises critical concerns regarding their environmental impact and potential toxicity, hindering their commercial development. In response to these concerns, researchers have devoted considerable effort towards the development of environmentally‐friendly perovskites. In this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 267 publications
0
3
0
Order By: Relevance
“…Therefore, the theoretical understanding provides insights into the electronic structure of perovskites and explains the results in the PL emission peak originating from the Pb inner band. It is worth noticing that the exact location and nature of electronic states within the material's band gap can be complex and may vary depending on the perovskite composition and environmental conditions [ 73 ]. Resultingly, the origin of the significant PL emission peak in the Pb inner band is likely based on the combination of experimental evidence and theoretical understanding.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the theoretical understanding provides insights into the electronic structure of perovskites and explains the results in the PL emission peak originating from the Pb inner band. It is worth noticing that the exact location and nature of electronic states within the material's band gap can be complex and may vary depending on the perovskite composition and environmental conditions [ 73 ]. Resultingly, the origin of the significant PL emission peak in the Pb inner band is likely based on the combination of experimental evidence and theoretical understanding.…”
Section: Resultsmentioning
confidence: 99%
“…Relevant studies have confirmed the biotoxicity of lead. , Therefore, solving the lead toxicity problem is a research focus in the development of halide perovskite luminescent materials. An effective strategy for developing lead-free halide perovskite materials is to use environmentally friendly metal ions to directly replace lead. At present, researchers have gained a lot from the application of lead-free halide perovskites on advanced displays and light-emitting diodes. In 2018, Tan et al synthesized a lead-free inorganic halide perovskite Cs 2 SnCl 6 : Bi with blue light emission, which has a PLQY of up to 80% and excellent thermal and water stability .…”
Section: Introductionmentioning
confidence: 99%
“…With increasing importance focused on environmental protection, the fields of lighting and display are more inclined to choose environmentally friendly materials. Lead-free double perovskites are among the top choices due to their nontoxicity and high stability, making them favored by researchers. However, lead-free double perovskites suffer from low luminescence efficiency, posing a challenge in obtaining highly efficient emission.…”
Section: Introductionmentioning
confidence: 99%